2003
DOI: 10.1007/s00204-002-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric determination of novel organotellurium compound toxicity in a promyelocytic (HL-60) cell line

Abstract: The increasing use of tellurium compounds in organic synthesis, industrial applications, and as a possible component in pesticides means that its introduction into the environment will increase in the future. Therefore, knowledge of the relative toxicity and mode of toxic action of tellurium-containing compounds is important. The studies detailed here used three model compounds: diphenyl ditelluride, 3,3'-diaminodiphenyl ditelluride, and 4,4'-diisopropyldiphenyl ditelluride. Experiments with human promyelocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Moreover, it was described that the compound AS101 may be involved in G2/ M growth arrest and induced apoptosis in multiple myeloma [30]. Consistently, DPDT treatment induced a time-dependent increase in the number of apoptotic cells from the S and G2/ M portions of the cell cycle in HL-60 cells [3]. This suggests that DPDT interferes either with DNA replication or with cell division processes.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Moreover, it was described that the compound AS101 may be involved in G2/ M growth arrest and induced apoptosis in multiple myeloma [30]. Consistently, DPDT treatment induced a time-dependent increase in the number of apoptotic cells from the S and G2/ M portions of the cell cycle in HL-60 cells [3]. This suggests that DPDT interferes either with DNA replication or with cell division processes.…”
Section: Discussionmentioning
confidence: 73%
“…For this, we applied the enzymatic morphological analysis that showed dose-dependent induction of apoptosis and necrosis at all time periods studied (table 2). Sailer et al [3] demonstrated a cell cycle-specific (from S and G2 phase) apoptosis induction in HL-60 cells after DPDT exposure. As caspases are important mediators of apoptosis [22], we determined apoptosis in DPDT-treated cells by the luminescence-based caspase 3/7 assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 However, to the best of our knowledge, the cytotoxicity profile of tellurium nanostructures has yet to be established.…”
Section: Introductionmentioning
confidence: 99%